COMBINATION BETWEEN MOVING BED REACTOR AND ACTIVATED SLUDGE PROCESS TO REMOVE HIGH ORGANIC LOADING OF SEAFOOD WASTEWATER - Manh, Do Van; Hoa, Truong Thi; Thoan, Nguyen Viet; Anh, Do Tuan; Minh, Nguyen Tuan; Tuan, Le Minh (Vietnam Journal of Science and Technology, 2017)
The combination of moving bed reactor and conventional activated sludge (pilot) process to treat seafood processing wastewater with high organic concentration was conducted in Ha Long Canned Food Factory. The pilot was designed automatic modul and treatment capacity of 2 m3/day. The removal ability of the organic content of the system reached 5 kg BOD5/m3.d. The obtained results indicate that the distingushing of organic (BOD5) removal efficiency between pilot and two orders activated sludge of Ha Long are 90-95 % and 45-50 %, respectively. Resulting from realistic and highly application study, the combination between moving bed biofilter and conventional activated sludge process shows the promissing acheivement for wastewater treatment of seafood processing industry in Viet Nam.